2021
DOI: 10.3390/socsci10120480
|View full text |Cite
|
Sign up to set email alerts
|

Gender Equality, Human Development, and PISA Results over Time

Abstract: Gender equality through the empowerment, representation, and provision of equal opportunities for all, regardless of gender, is increasingly recognised as a driver of social outcomes and a fundamental human right. This study explores the longitudinal (2006–2018) relationship between gender equality, human development, and education results as measured by PISA. Gender equality and human development are consistently correlated with PISA scores at each time point; however, when controlling for starting values and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Firstly, differences in academic performance according to sex, age, grade, and the schools’ level of performance were observed. These results are consistent with the existing literature [ 1 , 26 , 27 , 28 ]. For instance, a Spanish study with a sample of 535 students between 7 and 11 years old, showed that not only attitude, but also interest in schoolwork tends to decrease as the course progresses, which directly influences academic performance [ 29 ].…”
Section: Discussionsupporting
confidence: 94%
“…Firstly, differences in academic performance according to sex, age, grade, and the schools’ level of performance were observed. These results are consistent with the existing literature [ 1 , 26 , 27 , 28 ]. For instance, a Spanish study with a sample of 535 students between 7 and 11 years old, showed that not only attitude, but also interest in schoolwork tends to decrease as the course progresses, which directly influences academic performance [ 29 ].…”
Section: Discussionsupporting
confidence: 94%
“…That is, more effective schools could decrease and even mitigate the gender gap in achievement. Furthermore, a noteworthy result is that there was also a positive association between equity and parity; therefore, the schools with the highest parity would also be the most equitable [24]. This result suggests that improving educational processes in schools could improve the educational system in terms of social justice [3,7,30].…”
Section: Discussionmentioning
confidence: 99%
“…Among the aforementioned SDGs, the fifth proposes the need to "achieve gender equality and empower all women and girls" [3]. Improvements in gender equality, translated into greater representation of women in politics, a decrease in the maternal mortality rate or a decrease in teenage pregnancies, would be related to improved results in international tests such as the PISA for both male and female students [24]. These results would allow us to infer that countries concerned with reducing the gender gap between male and female students would have greater educational success.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on the impact of the COVID-19 pandemic and its relation to sustainability has been studied in various areas such, as the psychology of sustainability and quality of life (Keshky, Basyouni & Sabban, 2020;Özdemir and Kerse, 2020;Scheer and Laubenstein, 2021), animal welfare and livestock supply chain sustainability (Hashem, González-Bulnes & Rodriguez-Morales, 2020), the transformation of sustainability requirements of residential buildings (Tokazhanov et al, 2020), clean fuel programs and ensuring sustainability for household energy needs (Ravindra et al, 2021), supply chain discipline (Chowdhury et al, 2021), a gender-sensitive (Escalante and Maisonnave, 2021;Campbell, McIntyre, and Kucirkova, 2021), environmental effects of COVID-19 pandemic and potential strategies of sustainability (Rume & Islam, 2020), and integrated social protection strategies (Ratuva et al, 2021). In line with Ratuva et al (2021) and Rume and Islam (2020), who conclude that it is necessary to use local culture as a strategy to ensure sustainability, this paper elaborates an example of local culture in ensuring food security and economic sustainability in the face of the economic impact of COVID-19.…”
Section: Introductionmentioning
confidence: 99%